2013
DOI: 10.1002/jcph.165
|View full text |Cite
|
Sign up to set email alerts
|

ABCB1andABCC1variants associated with virological failure of first-line protease inhibitors antiretroviral regimens in Northeast Brazil patients

Abstract: The present study aims at evaluating the association between seven single nucleotide polymorphisms (SNPs) in five genes involved on antiretroviral pharmacokinetic pathways and virological failure in first line highly active antiretroviral therapy. Seven candidate polymorphisms (rs3842 and rs1045642 in ABCB1, rs212091 and rs3743527 in ABCC1, rs3745274 in CYP2B6, rs628031 in SLC22A1 and rs1517618 in SLCO3A1) were evaluated if they were associated with virological failure through logistic regression analysis. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
1
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(23 citation statements)
references
References 31 publications
0
21
1
1
Order By: Relevance
“…Though our study did not find a significant association, a study done in China found a significant association between ABCB1 C3435T polymorphism and CD4 cell count [5]. Another study found a significant relationship between ABCB1 C3435T polymorphism and virological failure especially for those on regimens containing protease inhibitors [18].…”
Section: Effect Of Abcb1 C3435t Genotypes On Clinical Outcomescontrasting
confidence: 88%
See 1 more Smart Citation
“…Though our study did not find a significant association, a study done in China found a significant association between ABCB1 C3435T polymorphism and CD4 cell count [5]. Another study found a significant relationship between ABCB1 C3435T polymorphism and virological failure especially for those on regimens containing protease inhibitors [18].…”
Section: Effect Of Abcb1 C3435t Genotypes On Clinical Outcomescontrasting
confidence: 88%
“…When adjusted for baseline ALT levels, the effect of ABCB1 C3435T genotypes on log ALT levels was not statistically significant (p = 0.122). After 6 months of therapy with lopinavir-based regimens (second-line regimen), the study participants with the CC genotype had lower median ALT levels of 16.7 [13][14][15][16][17][18][19][20][21] compared to those who had the CT genotype with a median ALT level of 25.5 . On univariate regression analysis, the effect of ABCB1 C3435T genotypes on log ALT levels was not statistically significant (p = 0.257).…”
Section: Effect Of Abcb1 C3435t Genotypes On Alt Levelsmentioning
confidence: 99%
“…Several of the hub genes had known associations with the pathology of colorectal mucosa. The most notable example was ABCB1, a transporter protein that interacts with several drugs and which has been genetically associated with the failure of first-line protease inhibitors in HIV-infected patients (40). Other important hub genes included RPS5, a ribosomal protein associated with colorectal cancer, and RNF186, a ring finger protein that has been genetically associated with ulcerative colitis (UC).…”
Section: Resultsmentioning
confidence: 99%
“…A Brazilian study of 187 HIV patients, among whom 27 were protease inhibitor nonresponders, were assessed for their MDR1 c.3435C>T genotype. Conversely, individuals carrying the c.3435T variant were more likely to fail first‐line HIV treatment regimens compared to those carrying a wild‐type allele …”
Section: Efflux Transporter Polymorphisms Of Potential Clinical Signimentioning
confidence: 99%
“…Conversely, individuals carrying the c.3435T variant were more likely to fail first-line HIV treatment regimens compared to those carrying a wild-type allele. 71 Moreover, the immunosuppressants and chemotherapeutics cyclosporine, methotrexate, and imantinib have been shown to be affected by genetic variation in MDR1. Renal transplant patients homozygous for the MDR1 c.3435T or the g.2677T variant had higher cyclosporine trough plasma concentrations compared to individuals carrying a wild-type allele.…”
Section: Efflux Transporter Polymorphisms Of Potential Clinical Signimentioning
confidence: 99%